The cost-effectiveness of improved brief interventions for tobacco cessation in Thailand - Palakai, Rungrat; Sornpaisarn, Bundit; Sawangdee, Yothin; Chuanwan, Sutthida; Saonuam, Pairoj; Katewongsa, Piyawat; Rehm, Jürgen (Frontiers in Public Health, 2023)
This study estimated the cost-effectiveness of four strategies enhancing the quality and accessibility of Brief Intervention (BI) service for smoking cessation in Thailand during 2022-2030: (1) current-BI (status quo), (2) the effective-training standard-BI, (3) the current-BI plus the village health volunteers (VHV) mobilization, and (4) the effective-training BI plus VHV mobilization. By interviewing five public health officers, nine healthcare professionals aiding these services, and fifteen BI service experts, we explored the status quo situation of the Thai smoking cessation service system, including main activities, their quantity assumptions, and activities' unit prices needed to operate the current cessation service system. Then, we modeled additional activities needed to implement the other three simulated scenarios. We estimated the costs and impacts of implementing these strategies over a nine-year operating horizon (2022-2030), covering three years of service system preparation and six years of full implementation.The modeled costs of these four strategies included intervention and program costs. The study focused on current smokers age 15 years or older. The assessed impact parameters encompassed smoking prevalence, deaths averted, and healthy life-years gained. An Incremental Cost-Effectiveness Analysis compared the four simulated strategies was employed. Data analysis was performed using the One Health Tool software, which the World Health Organization developed.The findings of this investigation reveal that all three intervention strategies exhibited cost-effectiveness compared to the prevailing status quo. Among these strategies, Strategy 2, enhancing BI service quality, emerged as the most efficient and efficacious option. Therefore, the expansion of quality services should be synergistically aligned with augmented training, service delivery optimization, and managerial enhancements. This approach is particularly poised to enhance accessibility to and the efficacy of smoking cessation interventions across Thailand.